2020
DOI: 10.1111/gcb.15205
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost nitrogen status and its determinants on the Tibetan Plateau

Abstract: Permafrost underlies approximately 24% of the land area of the Northern Hemisphere (Zhang, Barry, Knowles, Heginbottom, & Brown, 1999). Over the past decades, climate warming has occurred continuously in permafrost regions (Biskaborn et al., 2019; Hu et al., 2019), with global permafrost temperature increasing by about 0.3°C per decade (Biskaborn et al., 2019). The warming climate has induced widespread permafrost thaw (Chadburn et al., 2017; Ran, Li, & Cheng, 2018), which may trigger considerable amounts of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 78 publications
2
62
0
2
Order By: Relevance
“…Inorganic nitrogen content was significantly less under year‐round warming (Figure 1c) indicating nitrogen limitation due to climate change in Tibetan alpine meadow ecosystems previously recognized by Ding et al (2019) that may be exacerbated by drought stress. A recent large‐scale field investigation along a 1000‐km transect in the Tibetan Plateau revealed that gross rates of N mineralization were positively associated with soil moisture (Mao et al, 2020). Microbial residues are comparatively rich in nitrogen (Cotrufo et al, 2015) and fungal residues (derived from chitin) are considered to be more persistent than bacterial residues (derived from peptidoglycan; Ding et al, 2019; Six et al, 2006) making the latter more susceptible to nitrogen mining during the growing season.…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic nitrogen content was significantly less under year‐round warming (Figure 1c) indicating nitrogen limitation due to climate change in Tibetan alpine meadow ecosystems previously recognized by Ding et al (2019) that may be exacerbated by drought stress. A recent large‐scale field investigation along a 1000‐km transect in the Tibetan Plateau revealed that gross rates of N mineralization were positively associated with soil moisture (Mao et al, 2020). Microbial residues are comparatively rich in nitrogen (Cotrufo et al, 2015) and fungal residues (derived from chitin) are considered to be more persistent than bacterial residues (derived from peptidoglycan; Ding et al, 2019; Six et al, 2006) making the latter more susceptible to nitrogen mining during the growing season.…”
Section: Discussionmentioning
confidence: 99%
“…We selected 24 sites across the central and north of the Tibetan Plateau in 2016 (Figure 1). For each site, five soil cores were gathered within a 10 m × 10 m plot as described in Mao et al (2020). Specifically, soil cores were sampled using a borehole drilling machine with a bore head of 10 cm diameter.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 120 samples were collected from the permafrost layer across 24 sites. Among these sites, the sampling depth varied between 1.5 and 3.5 m due to the fact that the observed ALT ranged from 0.7 to 2.9 m (Mao et al, 2020). Before experimental analyses, the obtained five replicates from each site were cut into segments, and then mixed with an equal quality to form a composite sample.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were then analysed with a gas chromatograph (Agilent 6850, Agilent Technologies) and the MIDI Sherlock Microbial Identification System (Microbial ID Inc.) to determine the amount and classification of the PLFAs, respectively. PLFAs specific to fungi (18:2ω6, 9c) and bacteria (i14:0, i15:0, a15:0, i16:0, a17:0, i17:0, 16:1ω7c, cy‐17:0, 18:1ω7and cy19:0; Frostegård & Bååth, 1996; Mao et al., 2020) were used to calculate F/B. With regard to soil extracellular enzyme activity, we measured hydrolase and oxidase activities which were responsible for labile and recalcitrant carbon decomposition (Allison et al., 2008), respectively.…”
Section: Methodsmentioning
confidence: 99%